An Analysis of Bullying in Three Children Books by Trudy Ludwig - Alya Inayyah (Passage, 2021)
Bullying is a phenomenon that is commonly known in society. It usually refers to an act of someone hurting other people intentionally. The depiction of bullying includes unpleasant actions to someone. Bullying is present in the stories titled My Secret Bully (2005), Just Kidding (2006), and Trouble Talk (2008) by Trudy Ludwig which are the subject of this text analysis. The purpose of this study is to understand the representation of acts of bullying in the stories along with meanings construed from it. Using the story scripts as its data source, this study is consequently qualitative, employing textual analysis to explore the data. The study uses Hall’s (1997) theory of representation and Foucault’s (1982) theoretical framework of power. Based on the analysis, the study finds that power is used by the bullies, the bullied, and adults for their own respective interests. The study reveals that children have the potential to bully and adults' role is essential in handling bullying. It is also implied that adults should play a more active role and should not underestimate children’s discourse. Therefore, this study signifies an awareness-raising on the bullying issue and that the notion of power play can be found in children’s discourse.